The study of consistent properties of the vasopressin nasal dosage form - Al Nukarii Abdulkarim; A. L. Drozdov; A. P. Lysyanskaya (Zaporozhye State Medical University, 2016)
Evaluation of consistent properties is an important and integral part of investigations on the creation of semisolid nasal pharmacotherapeutic agents. The aim of this work is the study of consistent properties of developed nasal semisolid dosage form with synthetic analogue of vasopressin - arginine-vasopressin for the treatment of cognitive consequences of cerebral-vascular pathology. Materials and methods. The study of structural-mechanical characteristics of nasal ointment with 0.000005% arginine-vasopressin on the vaseline-lanolin-paraffin base was carried out by a rotary viscosimeter «Reotest-2» with cylindrical arrangement. It was established that consistent properties of arginine-vasopressin semisolid dosage form and «mechanical stability» (2.56) describe composition as a thixotropic system which provides with restorability after applying tension and allow to predict stability of consistent properties during a long-term storage. Calculated factors of dynamical flowing of arginine- vasopressin dosage form on the vaseline-lanolin-paraffin base (Кd1=28.7%; Kd2=53.84%) quantitatively confirm satisfactory spreading degree of the system during application on the mucous membranes or in manufacturing process. Conclusions. The studies of consistent properties of nasal ointment with synthetic analogue of vasopressin - arginine-vasopressin 0.000005% on lipophilic basis for treatment of cognitive effects of cerebrovascular disease have been conducted by rotary viscometer «Reotest 2». It has been established that consistent properties of studied soft nasal dosage form of arginine-vasopressin and «mechanical stability» value of the system (2.56) characterize it as a thixotropic, that assure recovery from mechanical stress, that allows to predict the stability of consistent properties of the composition during prolonged storage. The calculated values of coefficients of dynamic flow of intranasal dosage form of arginine-vasopressin on vaseline-lanolin-paraffin base (Кd1=28.7%; Kd2=53.84%) quantitatively confirm satisfactory level of system distribution during application on mucous membranes or at manufacturing process operations.